Safety and Performance of OptiVantage, a CT Contrast Media Injector, in Multi-Patient Mode - Tirri, Angela; Iannelli, Filippo; Sequeira, Anthony; Hebert, Frantz (Lung cancer (Auckland), 2025)
To evaluate the safety, performance and user's satisfaction of OptiVantage , a dual head CT Contrast Delivery System, in multi-patient mode for patients requiring a contrast-enhanced CT examination. A total of 100 subjects were included in this multicentre observational clinical investigation, conducted between April 20, 2023, and October 6, 2023. The primary endpoint for safety was the rate of extravasation, and the primary endpoint for performance was the success of injection assessed by the investigator. Secondary endpoints for safety were the rates of air embolism and sepsis as well as adverse events (AE) related to the injection. Other data collected included indication, set-up time, injection parameters and user's satisfaction. The study population included 59% of women. The mean age was 63.6 ± 12.7 years (range: 18 to 83 years), with the majority of patients (55%) older than 65 years. The main indications for undergoing contrast-enhanced CT were breast cancer, colon cancer and lung cancer or nodules. The mean volume injected was 119.5 ± 14.4 mL and the injection rate ranged from 2.8 to 4.5 mL/s (mean; 3.6 ± 0.3 mL/s). No extravasation or other adverse event, including air embolism and sepsis, was reported in any of the subjects (95% CI: [0.00%, 3.62%]). All the injections (100%; 95% CI: 95.39%, 100.00%) were considered as successful for the obtention of diagnostic images. The preparation of the subject, including the setting of the patient line, took between 6 and 10 seconds in most cases (68%) and 16 to 20 seconds for 30 patients (30%). The dayset was changed for 15 subjects and in all cases, it took no more than one minute. In conclusion, this study confirms the safety and performance of the OptiVantage Dual head in multi-use mode for contrast injection in adult patients, particularly elderly, undergoing contrast-enhanced CT.